Philosophical Markers of Being in the Novel “Elegant Hedgehog” by Muriel Barberу - Bovsunivska, Tetyana (Pitannâ lìteraturoznavstva, 2013)
The article deals with the design features of philosophical novel in the creations of french writer Muriel Barbery. The plot is simple, but there is much more to this book than that. It reminds you of so many things that make life wonderful – art, literature, music, ideas and so many wonderful small things. Considered the leading features of philosophical novel since the Enlightenment and to postpostmodernism relates to text. Analyzes the main philosophical allusions (to the philosophy of Marx, Husserl, Ozu, Kant, others), opposition (adult world / world of childhood, life / death, true philosophy / philosophy imitation), simulate (children's suicide, genuine beauty, imitation thoughts) reflections in the novel “The elegance of the hedgehog” by Barbery. Details the principle of deployment of dilemmas in the novel. This novel is characterized by a game statuses: the concierge is a philosopher; a twelve year old girl intellectually superior graduate bachelor; professor can only sign the invitations. Interpreted the E. Shevyakova`s term “intergenre Novel poly form”, recreated philosophical context of the writer, her preferences and dislikes regarding various philosophies and representatives. Accentuated ideological the confrontation of Barbery`s novel with regard to postmodern worldview. The novel was adapted into a film “The Hedgehog” (“Le hérisson”) released in 2011, starring Josiane Balasko as Michel, Garance Le Guillermic as Paloma, and Togo Igawa as Kakuro Ozu.